2008
DOI: 10.1111/j.1365-2133.2008.08582.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide synthases in pemphigus vulgaris in a mouse model

Abstract: SUMMARYBackground: Pemphigus vulgaris (PV) is a blistering autoimmune disease characterized by IgG autoantibodies against desmoglein 3. Nitric oxide synthases (NOS) may contribute to the increase of inflammation in tissues by the generation of nitrotyrosine residues (NTR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Also, it has been demonstrated that PV-IgG induces EGFR activation, and EGFR inhibition prevents acantholysis (11,35). These issues are in line with our previous observation that the tyrosinekinase (TK) inhibitor genistein inhibited nNOS expression induced by PV-IgG (28). Here, we observed that PV-IgG increased nNOS expression in a HER isoform-dependent way.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, it has been demonstrated that PV-IgG induces EGFR activation, and EGFR inhibition prevents acantholysis (11,35). These issues are in line with our previous observation that the tyrosinekinase (TK) inhibitor genistein inhibited nNOS expression induced by PV-IgG (28). Here, we observed that PV-IgG increased nNOS expression in a HER isoform-dependent way.…”
Section: Discussionsupporting
confidence: 91%
“…The free radical NO may react with the superoxide anion (O 2 À ) to produce the tissue-damaging agent peroxynitrite, which may rapidly nitrate tyrosine residues in proteins to form nitrotyrosine residues (NTR) (26,27). Our group has previously demonstrated that nNOS plays a relevant role in PV acantholysis using a mouse model (28). Usually, nNOS was expressed in a constitutive form in the basal cells of the epidermis, with increased levels of expression following exposure of the epidermis to PV-IgG.…”
Section: Introductionmentioning
confidence: 98%
“…Acantholysis can be blocked both by inhibitors of signaling kinases, such as p38 MAPK (3), mammalian target of rapamycin (4), Src, and epidermal growth factor receptor (EGFR) kinase (2, 4 -7) and by other tyrosine kinases, phospholipase C, calmodulin, and protein kinase C (8,9), as well as inhibitors of executioner caspases (4,10,11). The inhibitors of EGFR, Src, p38 MAPK, and mammalian target of rapamycin, can also abolish PVIgG-dependent activation of the apoptotic pathways in KCs (4,12).…”
Section: Pemphigus Vulgaris (Pv)mentioning
confidence: 99%
“…The serum factors implicated in apoptolysis include Fas ligand (FasL) (14), tumor necrosis factor ␣ (15,16), interleukins 1, 6, 8, and 15 (15,(17)(18)(19), nitric oxide (9,20), kallikreins, and other proteases (21). Using an organ culture model of PV, it has been demonstrated that PVIgG works together with FasL and tumor necrosis factor ␣ to induce apoptolysis (22).…”
Section: Pemphigus Vulgaris (Pv)mentioning
confidence: 99%
“…We have observed that iNOS expression is enhanced in patients with pemphigus vulgaris [33] with a role in the pathogenesis of the disease contributing to the increase of inflammation in tissues by the generation of nitrotyrosine residues [34]. The formation of 3-nitrotyrosine in proteins creates new epitopes that can elicit both humoral and cellular immune response.…”
Section: Discussionmentioning
confidence: 98%